Exploring the experiences of frontline nurses during the first 6 months of the COVID‐19 pandemic: An integrated literature review - Megan R. Jackson; Joanne E. Porter; Christopher Mesagno (Wiley, 2023)
Abstract Aim The aim of this study was to explore the experiences of frontline nurses caring for patients during the first 6 months of the COVID‐19 pandemic. Design The JBI manual for evidence synthesis and the PRISMA guidelines for reporting. Data sources CINAHL Complete, MEDLINE, PsycINFO (EBSCO) and Scopus (Elsevier). Review Methods The JBI Mixed Methods Data Extraction Tool following a Convergent Integrated Approach. Results Nineteen studies were included in the review, comprising eight countries and 2525 frontline nurses. Six themes emerged encompassing frontline nurses' COVID‐19 experiences including emotional experiences, physical symptoms, ethical and moral challenges, professional impact, risk factors for negative emotional experiences and protective factors for future pandemic events. Conclusion Frontline nurses have faced numerous challenges during the COVID‐19 pandemic. Providing frontline nurses with the required resources and support to perform their roles in global healthcare crises allows for an empowered and resilient workforce ensuring nurses remain in their chosen profession.